2010
DOI: 10.1111/j.1462-2920.2010.02354.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo expression of virulence genes in Vibrio isolates belonging to the Harveyi clade in relation to their virulence towards gnotobiotic brine shrimp (Artemia franciscana)

Abstract: Vibrios belonging to the Harveyi clade are pathogenic marine bacteria affecting both vertebrates and invertebrates, thereby causing a severe threat to the aquaculture industry. In this study, the expression of haemolysin, metalloprotease, serine protease, the quorum sensing master regulator LuxR and the virulence regulator ToxR in different Harveyi clade isolates was measured with reverse transcriptase real-time PCR with specific primers. There was relatively low variation in the in vitro expression levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 54 publications
2
36
0
Order By: Relevance
“…Shrimp-associated wild-type Vibrio harveyi showed a peak in quorum sensing activity early during infection-well before the first mortality is observed. This is consistent with our previous work, in which we found that there is a peak in expression of the quorum sensing master regulator gene luxR and different virulence genes early during infection of brine shrimp larvae (Ruwandeepika et al, 2011b). The in vivo quorum sensing activity of mutants defective in the production of one of the three signal molecules is consistent with their virulence, with no detectable in vivo quorum sensing activity in AI-2-and CAI-1-deficient mutants.…”
Section: Harveyi Quorum Sensing During Shrimp Infectionsupporting
confidence: 81%
See 1 more Smart Citation
“…Shrimp-associated wild-type Vibrio harveyi showed a peak in quorum sensing activity early during infection-well before the first mortality is observed. This is consistent with our previous work, in which we found that there is a peak in expression of the quorum sensing master regulator gene luxR and different virulence genes early during infection of brine shrimp larvae (Ruwandeepika et al, 2011b). The in vivo quorum sensing activity of mutants defective in the production of one of the three signal molecules is consistent with their virulence, with no detectable in vivo quorum sensing activity in AI-2-and CAI-1-deficient mutants.…”
Section: Harveyi Quorum Sensing During Shrimp Infectionsupporting
confidence: 81%
“…As brine shrimp are particle filter feeders, the challenge procedure allows infection to develop in a natural way, with the vibrios being accumulated in the gastro-intestinal tract and causing damage to the gut epithelium (Gunasekara et al, 2012). Recently, we developed an experimental procedure allowing us to measure virulence gene expression of vibrios in vivo during infection of brine shrimp larvae and found that the Vibrio harveyi quorum sensing master regulator gene luxR showed a peak in in vivo expression levels in virulent isolates early during infection, whereas the expression levels remained low in an avirulent isolate (Ruwandeepika et al, 2011b). However, to obtain good quantification, we needed to take 500 larvae per sample for these analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression was determined with qRT-PCR as described previously [31]. V. anguillarum cultures grown in LB 20 medium were collected at 6 h, 12 h and 24 h. Three different V. anguillarum cultures were sampled for each treatment.…”
Section: Methodsmentioning
confidence: 99%
“…vscP ) [30] and exoproteolytic activity (e.g. vhp ) [17,31], in addition to bioluminescence (using the lux system) [32]. …”
Section: Introductionmentioning
confidence: 99%